Private security and the investigative process - Nemeth, Charles P., 1951- (CRC Press : Auerbach Publications, 2010)
Detailing best practices and trade secrets for private sector security investigations, Private Security and the Investigative Process, Third Edition provides complete coverage of the investigative process. Fully updated, this edition covers emerging technology, revised legal and practical considerations for conducting interviews, and new information on case evaluation. Written by a recognized expert in security, criminal justice, ethics, and the law-with over three decades of experience-the updated edition of this popular text covers concepts and techniques that can be applied to a variety of i.